TRANSCRIPT OF HOUSE HEALTH & LIFE SUBCOMMITTEE - HOUSE BILL 1456 890424 (Tufts Archival Research Center, 2007)
Transcript from a meeting in the House Health and Life Committee regarding a bill requiring newly hired fire fighters tobacco free for a year before their employment. Includes testimony from a representative from RJ Reynolds arguing that it would be an infringement on the right to privacy.